Dickeya undicola sp. nov., a novel species for pectinolytic isolates from surface waters in Europe and Asia. Issue 8 (5th June 2019) - Oulghazi, Saïd; Pédron, Jacques; Cigna, Jérémy; Lau, Yin Yin; Moumni, Mohieddine; Van Gijsegem, Frédérique; Chan, Kok-Gan; Faure, Denis
Abstract : Strains 2B12 T, FVG1-MFV-O17 and FVG10-MFV-A16 were isolated from fresh water samples collected in Asia and Europe. The nucleotide sequences of the gapA barcodes revealed that all three strains belonged to the same cluster within the genus Dickeya . Using 13 housekeeping genes ( fusA, rpoD, rpoS, glyA, purA, groEL, gapA, rplB, leuS, recA, gyrB, infB and secY ), multilocus sequence analysis confirmed the existence of a new clade. When the genome sequences of these three isolates and other Dickeya species were compared, the in silico DNA–DNA hybridization and average nucleotide identity values were found to be no more than 45.50 and 91.22 %, respectively. The closest relative species was Dickeya fangzhongdai . Genome comparisons also highlighted genetic traits differentiating the new strains from D. fangzhongdai strains DSM 101947 T (=CFBP 8607 T ) and B16. Phenotypical tests were performed to distinguish the three strains from D. fangzhongdai and other Dickeya species. The name Dickeya undicola sp. nov. is proposed with strain 2B12 T (=CFBP 8650 T =LMG 30903 T ) as the type strain.